IMPLEMENTASI PERATURAN DAERAH NOMOR 21 TAHUN 2012 TENTANG PENGELOLAAN SAMPAH DI KECAMATAN PADANG UTARA KOTA PADANG - Harsya, Irfan; ", ErnawatI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The consumption patterns of high society will impact on the amount of production waste generated, no exception to that occuring in the District North Padang. The District North Padang as one of the District in the Padang City lot of rubbish both derived from household waste and non-household. The trash are not managed properly will lead to a variety of diseases that can be contracted in the community and reduce the beuty of the city. Therefore, the Padang municipality passed a law number 21 of 2012 on waste management, which regulates how to manage waste that is good and right and provide sanctions for Rp.5000.000 to the public who are caught littering. Purpose of this research is to investigate the implementationn of regional regulation number 21 of 2012 on waste management in the district nort padang of the padang city. Used theoretical concepts using theories Edward III that covers aspects of communication, resources, disposition and bureaucratic structure . this study uses qualitative research methods to study descriptive data. In the data collection reseachers use interviewing techniques, obeservatio and documentation. By using purposive sampling method in that sample is designed by researches and triangulation techniques as a source of data authenticty. The results of this research showed that the implementation of legislation waste is still not running optimally because there are still some obstacles. Factor - inhibiting factor in the implementation of Regional Regulation No. 21 of 2012 on waste management in the district of Padang Padang Utara is Policy Implementor of Garbage Worker Performance remains low, Fasilities and infrastructure that is trash, Motor Tricycles that is still not enough and Public Participation is still low.Key Words : Communication, Resource, Disposition, Bureaucratic Structure